Survival benefit of active surveillance for papillary thyroid carcinoma: a propensity score matching analysis based on SEER database - Bi, Jinzhe; Lyu, Peng-fei; Wang, Yu; Zhang, Hao (Frontiers in Oncology, 2023)
Background: Although active surveillance (AS) has been proposed as an alternative treatment to immediate surgery for PTMC, its inclusion criteria and mortality risk have not been clearly defined. The purpose of this study was to investigate whether surgery can achieve significant survival benefits in patients with larger tumor diameter of papillary thyroid carcinoma (PTC), in order to evaluate the feasibility of expanding the threshold for active surveillance. Methods: This study retrospectively collected data of patients with papillary thyroid carcinoma from the Surveillance, Epidemiology, and End Results (SEER) database between 2000 and 2019. The propensity score matching (PSM) method was used to minimize confounding factors and selection bias between the surgery and non-surgery groups, and to compare the clinical and pathological characteristics between the two groups based on the SEER cohort. Meanwhile, the impact of surgery on prognosis was compared using Kaplan-Meier estimates and Cox proportional hazard models. Results: A total of 175,195 patients were extracted from the database, including 686 patients who received non-surgical treatment, and were matched 1:1 with patients who received surgical treatment using propensity score matching. The Cox proportional hazard forest plot showed that age was the most important factor affecting overall survival (OS) of patients, while tumor size was the most important factor affecting tumor-specific survival (DFS) of patients. In terms of tumor size, there was no significant difference in DFS between PTC patients with tumor size of 0-1.0cm who underwent surgical treatment and those who underwent non-surgical treatment, and the relative survival risk began to increase after the tumor size exceeded 2.0cm. Moreover, the risk of death increased over time, and no plateau phase was observed. Conclusions: For patients with papillary thyroid carcinoma (PTC) staged as T1N0M0, AS is a feasible management strategy. As the tumor diameter increases, the risk of death without surgical treatment gradually increases, but there may be a threshold. Within this range, a non-surgical approach may be a potentially viable management strategy. However, beyond this range, surgery may be more beneficial for patient survival. Therefore, it is necessary to conduct more large-scale prospective randomized controlled trials to further confirm these findings.